Natural Suppression of Rhizoctonia Bare Patch in a Long-Term No-Till Cropping Systems Experiment - Schillinger, W F (Plant disease, 2014)
The soilborne fungus Rhizoctonia solani AG-8 is a major concern for farmers who practice no-till in the inland Pacific Northwest of the United States. Bare patches caused by Rhizoctonia spp. first appeared in 1999 during year 3 of a 15-year no-till cropping systems experiment near Ritzville, WA (269 mm of annual precipitation). The extent and pattern of patches were mapped each year from 1999 to 2012 at the 8-ha study site with a backpack-mounted global positioning system equipped with mapping software. Bare patches appeared in winter and spring wheat (SW; Triticum aestivum), spring barley (SB; Hordeum vulgare), yellow mustard (Brassica hirta), and safflower (Carthamus tinctorius). At its peak in years 5 to 7, bare patches occupied as much as 18% of total plot area in continuous annual monoculture SW. The area of bare patches began to decline in year 8 and reached near zero levels by year 11. No measurable patches were present in years 12 to 15. Patch area was significantly greater in continuous SW compared with SW grown in a 2-year rotation with SB. Additionally, the 15-year average grain yield for SW in rotation with SB was significantly greater than for continuous SW. Russian thistle (Salsola tragus), a troublesome broadleaf weed with a fast-growing tap root, was the only plant that grew within patches. This article reports the first direct evidence of natural suppression of Rhizoctonia bare patch with long-term no-till in North America. This suppression also developed in a rotation that contained broadleaf crops (yellow mustard and safflower) in all but 5 years of the study, and the suppression was maintained when safflower was added back to the rotation